Inovasi Kreatif Lidi Kelapa Sawit dalam Membantu Pertumbuhan Ekonomi Masyarakat Desa di Kecamatan Pematang Bandar, Kabupaten Simalungun - Wulan Dayu; Hartato Rianto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
As part of efforts to boost the economic vitality of the village communities in Pematang Bandar district of Simalungun Regency, public awareness of the use of palm leaves for sticks has encouraged entrepreneurs to develop crafts by processing palm leaves into sticks. It provides an opportunity to open a product workshop and lead to a variety of products. processed. High quality handicraft shape. The craft of processing palm sticks is very promising if you reach the right target market with the right strategy and advice. The purpose of this service activity is to see how stakeholder perspectives and strategies of oil palm artisans are implemented to support economic growth of rural communities in Pumatan Bandar District, Simalungun District. The SWOT analysis method uses joint engagement and research techniques. From the results of the activities, the village community-run handicraft shop of palm oil sticks in Pematang Bandar district of Simalungun Regency is very promising with increased sales, number of consumers' interest and wide market share. The use of palm oil sticks in crafts has the potential to support economic growth in the community. Therefore, one viable strategy is to open production cooperatives to improve services and increase the quality and consumer confidence of products made from palm oil sticks. In addition, this palm oil stick handicraft business is considered creative and productive as it can generate employment for the community, which helps to promote economic growth in the community.